Pengaruh Kinerja BUMDes terhadap Penguatan Ekonomi Masyarakat Desa Sei Limbat, Kecamatan Selesai, Kabupaten Langkat - Ulen Bangun (MAN 4 Kota Pekanbaru, 2026)
This study examines the effect of Village-Owned Enterprises (BUMDes) on improving the local economy in Sei Limbat Village, Selesai Subdistrict, Langkat Regency. BUMDes functions as a community-based economic institution that manages village resources and business units to support rural welfare and economic independence. This research employed a quantitative approach using survey data collected through questionnaires distributed to BUMDes members across six hamlets. The instrument was tested using validity and reliability procedures, and the data were analyzed using simple linear regression. The findings show that BUMDes has a positive and significant effect on improving the community’s economic condition, reflected in increased income opportunities, higher participation in productive economic activities, and improved access to basic services. These results indicate that strengthening institutional management and business governance of BUMDes can become an effective strategy to promote inclusive rural economic development.